Endometrial Injury Upregulates Expression of Receptivity Genes in Women with Implantation Failure - Celik, Onder; Yurci, Arzu; Ersahin, Aynur; Gungor, Nur D.; Celik, Nilufer; Ozcil, Mustafa D.; Tinelli, Andrea (MDPI, 2023)
Background: Homeobox genes A10 (HOXA10) and A11 (HOXA11), members of the abdominal B gene family, are responsible for embryonic survival and implantation. This study was planned to investigate whether endometrial injury alters the expression of both transcripts in women with implantation failure. Methods: A total of 54 women with implantation failure were divided into two equal groups as experimental (scratching) and sham (no scratching). Participants in the scratching group were exposed to endometrial injury in the mid-luteal phase, and those in the sham group were exposed to endometrial flushing. The scratching group, but not the sham group, underwent prior endometrial sampling. A second endometrial sampling was performed on the scratching group in the mid-luteal phase of the following cycle. The mRNA and protein levels of the HOXA10 and 11 transcripts were determined in endometrial samples collected before and after injury/flushing. Participants in each group underwent IVF/ET in the cycle after the second endometrial sampling. Results: Endometrial injury caused a 60.1-fold (p < 0.01) increase in HOXA10 mRNA and a 9.0-fold increase in HOXA11 mRNA (p < 0.02). Injury resulted in a significant increase in both HOXA10 (p < 0.001) and HOXA11 protein expression (p < 0.003). There was no significant change in HOXA10 and 11 mRNA expressions after flushing. Clinical pregnancy, live birth, and miscarriage rates of the both groups were similar. Conclusions: Endometrial injury increases homeobox transcript expression at both mRNA and protein levels. © 2023 by the authors.
Keywords: endometrium; fertility outcome; homeobox gene; implantation failure; mRNA; protein